Crosstalk between gibberellin signaling and iron uptake in plants: an Achilles’ heel for modern cereal varieties? - von Wirén, Nicolaus; Bennett, Malcolm J. (Elsevier, 2016)
Plants utilize sophisticated morphological and physiological mechanisms to acquire iron from soil. In this issue of Developmental Cell, Wild et al. (2016) find that the hormone signal gibberellic acid is key in integrating these responses, raising questions about the impact of altering GA responses in modern cereal varieties on iron acquisition.